Higher Education Institutions in Peripheral Regions: A Literature Review and Framework of Analysis. Issue 4 (December 2017) - Kohoutek, Jan; Pinheiro, Rómulo; Čábelková, Inna; Šmídová, Michaela
Abstract This paper addresses the issue of universities' engagement in peripheral regions, taking into account both endogenous (university) and exogenous (regional peripherality) characteristics. The paper aims to deconstruct the university – periphery interplay in the form of a novel analytical framework and to pilot the framework empirically. The pilot mapping of six Norwegian and Czech universities onto the peripheral regions resulted in two implications. First, due to regional lag effects on the industrial – post-industrial development scale and institutional profiling, universities' regional role is contingent on path dependencies, suggesting that both exogenous and endogenous characteristics should be given equal consideration. Second, the universities' positioning in peripheral regional surroundings produces some variants in which universities' engagement is not pivotal for improving regional attributes. This is either because of the incapacity of unlocking the path-dependent effects of regional periphery structures or because of limitations in research capacity, constraining the respective regions' progress to the knowledge/service society paradigm. Further explorations of these issues may create an impetus for comparative studies on the role of universities in regional development, particularly with respect to peripheral units.